Heart Rate Variability Changes in Patients With Major Depressive Disorder: Related to Confounding Factors, Not to Symptom Severity? - Sarlon, Jan; Staniloiu, Angelica; Kordon, Andreas (Frontiers in Neuroscience, 2021)
ABSTRACT Background The aim of this study was to assess electrophysiological correlates of symptom severity and influencing factors in patients with Major Depressive Disorder (MDD) under three different conditions: baseline, stress exposure, and relaxation following stress exposure. Methods Symptom severity was assessed in 89 inpatients (32 females, mean age 51 years) with Major Depressive Disorder, using the Beck Depression Inventory (BDI-II; mean score 29.7 points). Resting heart rate (RHR), heart rate variability (HRV), respiration rate (RR), skin conductance (SC) and skin temperature (ST) were recorded for 300 seconds baseline, 60 seconds stress exposure and 300 seconds self-induced relaxation. As influencing factors, age, nicotine consumption, body mass index as well as blood pressure were evaluated. Results Disease severity correlated positively with SC elevation under stress exposure and with a lower RR in the relaxed state, but no association was found between HRV and symptom severity. Age and higher blood pressure were associated with lower HRV and higher RHR. Conclusions Results indicate that in MDD changes in the autonomous nervous system (ANS) are complex and the assessment of ANS reactivity to stressors is useful. Elevated blood pressure might be underdiagnosed, though relevant already in patients in the early 50ies, suffering MDD.